Altered shoulder kinematics using a new model for multiple dislocations-induced Bankart lesions. (December 2019) - Yoshida, Masahito; Takenaga, Tetsuya; Chan, Calvin K.; Musahl, Volker; Lin, Albert; Debski, Richard E.
Abstract: Background: Many active individuals undergo multiple dislocations during the course of a season before surgical treatment without considering the implications of each successive injury. Therefore, the purpose of this study was to develop a multiple dislocation model for the glenohumeral joint and evaluate the resulting changes in joint function. Methods: Eight cadaveric shoulders were evaluated using a robotic testing system. A simulated clinical exam was performed by applying a 50 N anterior load to the humerus at 60° of glenohumeral abduction and external rotation. Each joint was then dislocated. The same loads were applied again and the resulting kinematics were recorded following each of 10 dislocations. The force required to achieve dislocation was recorded and capsulolabral status was assessed. Findings: A reproducible Bankart lesion was repeatedly created following the dislocation protocol. The force required for all dislocations significantly decreased following the 1st dislocation. In addition, even lower forces were required to achieve the 5th and subsequent dislocations ( p < 0.05). Anterior translation in response to an anterior load during the simulated clinical exam increased between the intact and injured joints ( p < 0.05). However, anterior translation reached a plateau following the 3rd to 10th dislocations and was increased compared with the 1st dislocation ( p < 0.05). Interpretation: A repeatable Bankart lesion was not surgically made, but created by our new dislocation model. Joint function appeared to reach a constant level after the 3rd to 5th dislocations. Thus, multiple dislocations result in a deleterious dose dependent effect suggesting additional damage is not sustained after the fifth dislocation. Level of evidence: Controlled laboratory study. Highlights: Robotic testing system simulated multiple anterior dislocations of shoulder. Joint function was significantly affected by the first three dislocations. Multiple dislocations had deleterious dose dependent effect.